Hepatitis C Virus Testing Perspectives Among Primary Care Physicians in Four Large Primary Care Settings. Issue 2 (March 2015) - Jewett, Amy; Garg, Arika; Meyer, Katherine; Wagner, Laura Danielle; Krauskopf, Katherine; Brown, Kimberly A.; Pan, Jen-Jung; Massoud, Omar; Smith, Bryce D.; Rein, David B.
Background . In 1998, the Centers for Disease Control and Prevention (CDC) published Recommendations for Prevention and Control of Hepatitis C Virus (HCV) Infection and HCV-Related Chronic Disease, recommending HCV testing for populations most likely to be infected with HCV. However, the implementation of risk-based screening has not been widely adopted in health care settings, and 45% to 85% of infected U.S. adults remain unidentified. Objectives . To develop a better understanding of why CDC's 1998 recommendations have had limited success in identifying persons with HCV infection and provide information about how CDC's 2012 Recommendations for the Identification of Chronic Hepatitis C Virus Infection Among Persons Born During 1945-1965 may be implemented more effectively. Design . Qualitative data were collected and analyzed from a multidisciplinary team as part of the Birth Cohort Evaluation to Advance Screening and Testing for Hepatitis C project. Respondents . Nineteen providers were asked open-ended questions to identify current perspectives, practices, facilitators, and barriers to HCV screening and testing. Providers were affiliated with Henry Ford Hospital, Mount Sinai Hospital, the University of Alabama, and the University of Texas Health Science Center. Results . Respondents reported the complexity of the 1998 recommendations, and numerous indicated risk factors were major barriers to effective implementation. Other hindrances to hepatitis C testing included physician discomfort in asking questions about socially undesirable behaviors and physician uncertainty about patient insurance coverage. Conclusion . Implementation of the CDC's 2012 recommendations could be more successful than the 1998 recommendations due to their relative simplicity; however, effective strategies need to be used for dissemination and implementation for full success.